2018
DOI: 10.1002/mp.13150
|View full text |Cite|
|
Sign up to set email alerts
|

The utility of quantitativeCTradiomics features for improved prediction of radiation pneumonitis

Abstract: We have successfully incorporated CT radiomics features into a framework for building predictive RP models via LASSO logistic regression. Addition of normal lung image features produced superior model performance relative to traditional dosimetric and clinical predictors of RP, suggesting that pretreatment CT radiomics features should be considered in the context of RP prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 43 publications
0
82
0
Order By: Relevance
“…The addition of normal lung image features produced superior model performance with respect to traditional dosimetric and clinical predictors of radiation pneumonitis (RP), suggesting that pretreatment CT radiomic features should be considered in the context of RP prediction. CT radiomic features were extracted from the total lung volume defined using the treatment‐planning scan for RP …”
Section: Overview Of Research and Clinical Applications Of Cancer Radmentioning
confidence: 99%
“…The addition of normal lung image features produced superior model performance with respect to traditional dosimetric and clinical predictors of radiation pneumonitis (RP), suggesting that pretreatment CT radiomic features should be considered in the context of RP prediction. CT radiomic features were extracted from the total lung volume defined using the treatment‐planning scan for RP …”
Section: Overview Of Research and Clinical Applications Of Cancer Radmentioning
confidence: 99%
“…Radiomics is a developing research area that aims to extract more complex information from conventional medical images, such as computed tomography (CT) and magnetic resonance imaging, using features not easily visible to or quantifiable by the human eye . These features can then be used to build models of clinical outcomes, including diagnostic, prognostic, and predictive models …”
Section: Introductionmentioning
confidence: 99%
“…Parmar et al showed that radiomics‐based prediction with random forest machine learning had the highest area under the receiver operating characteristic (ROC) curve (AUC) of 0.66 . Although radiomics‐based approaches using various texture‐based features, such as intensity histograms, absolute gradients, nearest gray tone difference metrices, and gray‐level co‐occurrence matrices, have shown great potential for predicting the prognosis of cancer patients, there is still room for improving prediction accuracy …”
Section: Introductionmentioning
confidence: 99%
“…Multiple manuscripts have been published using radiomics to predict radiation response, in some cases with prediction power outperforming standard clinical variables (77)(78)(79)(80)(81)(82), though not in all (83). Radiomicsbased statistical approaches can predict various radiation normal tissue complication probabilities including radiation pneumonitis, xerostomia, and rectal wall toxicity (84)(85)(86)(87)(88)(89). Radiomics data, coupled with genomic data and increasingly computable clinical record data, may escort radiation oncology into a new epoch of truly personalized radiation plans based on patient-specific knowledge.…”
Section: Tumor Control Probability and Normal Tissue Complication Promentioning
confidence: 99%